In-use performance assessment of rendered autoclaved aerated concrete walls by long-term moisture monitoring - Kus, Hülya; Nygren, Kjell; Norberg, Peter (Elsevier BV, 2004)
The importance of long-term performance and durability of building materials and components has received increasing consideration with regard to a sustainable built environment. Degradation due to exposure to environment conditions, particularly driving rain, play a significant role in the service life of porous materials used in external wall components. Microenvironment monitoring data are presented in this paper to show how different surface coatings can contribute to moisture performance of external walls made of autoclaved aerated concrete (AAC). Renderings modified with hydrophobic products on AAC substrate prove to have less wetting and better drying properties than unmodified renderings according to the performance assessment based on the amount and duration of moisture measured in the material.